Serum activity of creatine kinase and aminotransferase aspartate enzymes of horses submitted to muscle biopsy and incremental jump test - Soares, Otavio Augusto Brioschi [UNESP]; Dángelis, Flora Helena de Freitas [UNESP]; Feringer Júnior, Walter Heinz [UNESP]; Nardi, Kamirro Bacciotti [UNESP]; Trigo, Pablo; Almeida, Fernando Queiroz de; Miranda, Ana Cláudia Tavares; Queirozneto, Antonio [UNESP]; Ferraz, Guilherme de Camargo [UNESP] (FapUNIFESP (SciELO), 2013)
The objective was to evaluate serum activity of the enzymes creatine kinase (CK) and aspartate aminotransferase (AST), which are leakage enzymes responsive to muscle injury, of athletic horses that underwent muscle biopsy and incremental jump test (IJT) involving incremental jumps. The animals were grouped as follows: the first group, horses with history of superior performance (SP); the second, with a history of inferior performance (IP); and lastly, a control group (CG). All groups underwent biopsy of the gluteus medius muscle, while groups SP and IP were also submitted to the incremental jump test (IJT) 24 hours after biopsy. The IJT consisted of three stages with 40 jumps each, where jump height increased progressively, from 40 to 60 and last, 80cm. Blood samples were drawn before biopsy, and 6 and 24 hours after the exercise as well. The levels of CK serum activity increased 6 hours after exercise and decreased 24 hours later in all groups, including CG. AST activity did not increase after biopsy and exercise. There was no increase of both enzyme activities that could be attributed to the exercise, possibly due to exercise short duration and/or low intensity. We conclude that the muscle biopsy was able to show that there was enough stimulus to cause CK enzyme leakage into the plasma, and consequent detection of increased serum activity, while the incremental jump test did not.
Keywords: Equestrian; Equine; Muscle enzymes; Performance test; Show jumping